Hypertension prevalence and control in Ulaanbaatar, Mongolia. Issue 1 (8th January 2020) - Potts, Harry; Baatarsuren, Uurtsaikh; Myanganbayar, Maral; Purevdorj, Baigal; Lkhagvadorj, Burtu‐Ujin; Ganbat, Namuun; Dorjpalam, Alimaa; Boldbaatar, Delgerbat; Tuvdendarjaa, Khulan; Sampilnorov, Dulmaa; Boldbaatar, Khatantuul; Dashtseren, Myagmartseren; et al.
Abstract: This study examines the prevalence, awareness, treatment, and control of hypertension in Ulaanbaatar, Mongolia, using both the American Heart Association and conventional thresholds (130/80 and 140/90 mm Hg, respectively). In this randomized cross‐sectional study, two‐stage cluster sampling was used to obtain a sample of 4515 individuals aged ≥20 years. Hypertension was defined by the use of antihypertensives in the last 2 weeks or a blood pressure at or above the thresholds of 140/90 and 130/80 mm Hg. The mean age of the participants was 41.1 ± 14.0 years and 54.5% were women. Hypertension prevalence was 25.6% (using 140/90 mm Hg) and 46.5% (using 130/80 mm Hg). Prevalence increased with age and below 50 years men were consistently more likely to be hypertensive. Among hypertensive participants, the rates of awareness, treatment, and control were 69.7%, 46.8%, and 24.0% (using 140/90 mm Hg) and 49.1%, 25.8%, and 6.4% (using 130/80 mm Hg, respectively). Men had lower rates of awareness, treatment, and control compared with women, with the most pronounced differences at younger ages. This study shows that awareness, treatment, and control rates in Ulaanbaatar are better than in most low‐ and middle‐income countries but are still suboptimal. The largest "care gap" was in young men where a regulatory requirement for annual workplace blood pressure screening has the potential to enhance care. A major hypertension control program has just been initiated in Ulaanbaatar.